Penggunaan Galur Lemah Chili veinal mottle virus untuk Proteksi Silang - Asniwita Asniwita; Sri Hendrastuti Hidayat; Gede Suastika; Slamet Susanto; Sriani Sujiprihati (Jurnal Fitopatologi Indonesia, 2013)
Inoculation of mild virus strain prior to severe virus strain to protect plant against viral disease is the principle of cross protection. Five mild strains of Chili veinal mottle virus (ChiVMV), i.e. -KAR, -SPR, -SKT, -CSR, and -PGL were used as cross protection agent to protect chili pepper plants against severe strain infection of ChiVMV-CKB. The mild strains were inoculated mechanically prior inoculation of severe strain and the efficiency of cross protection was evaluated by observing symptom development and measuring crop yield. Inoculation of mild strains 7 days prior inoculation of severe stain was not able to protect the plant from infection of severe strain ChiVMV-CKB. Protective effect was observed when mild strains were inoculated at 14, 21, and 28 days prior inoculation of severe strain. Symptom development was suppressed or delayed, and crop yield was not significantly different with healthy plants. It was suggested that to obtain the best protection against severe strain, the mild strain should be applied as early as possible before the occurrence of severe strain infection.